1997
DOI: 10.1021/la970767d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Intercalation of Alkali-Metal Ions into Birnessite-Type Manganese Oxide in Aqueous Solution

Abstract: A thin layer electrode of birnessite-type manganese oxide was prepared by brushing a mixed solution of KOCOCH3 and Mn(OCOCH3)2 on a platinum substrate, followed by heating at 1073 K. The chemical composition of the electrode was K x MnO y (x = 0.33 and y ∼ 2) with an interlayer spacing of c 0 = 0.697 nm. The positive-potential going sweep on the electrode in an aqueous phase caused the deintercalation of K+ with an increase in c 0. The quasi-reversible intercalation of K+ occurred with a subsequent negative-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 27 publications
11
89
3
Order By: Relevance
“…The approximate 7 Å interlayer distances are indicative of birnessite-type manganese oxides and the increased spacing associated with larger alkali metal cations is consistent with other studies involving synthetic birnessites [30].…”
Section: Characterizationsupporting
confidence: 89%
“…The approximate 7 Å interlayer distances are indicative of birnessite-type manganese oxides and the increased spacing associated with larger alkali metal cations is consistent with other studies involving synthetic birnessites [30].…”
Section: Characterizationsupporting
confidence: 89%
“…Thus, the redox pair observed at 0.60 V/0.30 V in powder Kbirnessite in K 2 SO 4 electrolyte has been assigned to the deintercalation/intercalation of K + from/into the K-birnessite lattice accompanied by the Mn 3+ oxidation/Mn 4+ reduction [6]. Kanoh et al [28] have reported a very complex mechanism for deintercalation/intercalation process in K-birnessite in aqueous KCl solution, where not K + , but H + is electrochemically active [28]. In that case the K-deintercalation (accordingly, K-intercalation) occurs by H 2 O intercalation followed by ion exchange between K + and H + [28].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Kanoh et al [28] have reported a very complex mechanism for deintercalation/intercalation process in K-birnessite in aqueous KCl solution, where not K + , but H + is electrochemically active [28]. In that case the K-deintercalation (accordingly, K-intercalation) occurs by H 2 O intercalation followed by ion exchange between K + and H + [28]. Another electrochemical studies on Kbirnessite in aqueous KCl and tetrabutylammonium chloride (TBACl) electrolytes evidence that both K + and H + play an important role in the electrochemical conversion between Mn 4+ and Mn 3+ [29].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…12,14,15,32,34 More recent EQCM reports examined MnOx pseudocapacitance phenomena and showed that cation insertion and ejection during reduction and oxidation, respectively, is the primary charge-compensation mechanism. 16,32,35 Traditional quartz crystal microbalance (QCM) experiments rely on the assumption that films are acoustically thin, thus allowing for gravimetric interpretation of the results using the Sauerbrey equation.…”
Section: Resultsmentioning
confidence: 99%